The influence of the sphere of physical culture and sports on life satisfaction - N. Y. Goncharova; E. A. Makarova (Путеводитель предпринимателя)
The article examines the assessment of the influence of the sphere of sports on the indicators of satisfaction and quality of life, and also examines these indicators themselves and the methodological approach to their formation. The article raises issues related to the assessment of the social effectiveness of investments in the development of physical culture and sports.